Self-assembly of random co-polymers for selective binding and detection of peptides. Issue 9 (5th January 2018) - Zhao, Bo; Serrano, Mahalia A. C.; Gao, Jingjing; Zhuang, Jiaming; Vachet, Richard W.; Thayumanavan, S.
Abstract : Amphiphilic random co-polymers, which form stable reverse micelle-type assemblies, have been shown to selectively extract and detect peptides. Abstract : Amphiphilic random co-polymers, which form stable reverse micelle-type assemblies, have been designed and synthesized. We demonstrate that the reverse micelles, formed by these co-polymers are capable of selectively binding peptides through electrostatic interactions, indicating that these random polymers can self-organize into functionally selective materials. Moreover, these random co-polymers also enable the ordered co-crystallization of matrix and extract guest molecules, giving rise to substantial signal enhancements during MALDI-MS detection. Together, these observations represent an excellent example of how random polymers can self-assemble into ordered, functional materials.